Curahan Waktu Kerja Wanita Tani Pada Usahatani Padi di Desa Purwokerto Kecamatan Ngimbang Kabupaten Lamongan - Miftah Nur Erina; Sri Widayanti; Nuriah Yuliati (Universitas Nahdlatul Ulama Blitar, 2026)
The imbalance in workload highlights that women farmers bear dual responsibilities, which limits the time they can allocate to rice farming activities, thereby affecting farm productivity. This study aims to analyze and describe the allocation of working hours between female and male farmers, the contribution of female farmers to productive and domestic activities, and the factors influencing women's labor time allocation in rice farming. The data were analyzed using descriptive methods and multiple linear regression based on the Cobb-Douglas model. The results show that the labor time contribution of women in rice farming amounts to 14 person-days per season, which is lower than that of men, who contribute 17.3 person-days per season. The proportion of women's labor time dedicated to productive activities is 16.1%, while 83.9% is allocated to domestic tasks. The variables that significantly and positively influence women's labor time in rice farming include household size, women’s wage rates, and land area. Age also significantly affects labor time allocation but has a negative relationship, indicating that older women tend to contribute fewer working hours.